STUDY ON SHARPENING OF CIRCULAR SAWS WITH STEEL TEETH (Innovation in Woodworking Industry and Engineering design, 2026)
The process of woodworking tools sharpening is a direct connection from the right choice of the abrasive tools form and its characteristics. Commonplace in companies of the woodworking and furniture industry are significant difficulties on the correct selection and use of abrasive tools. This is negatively affects on productivity and sharpening of cutting tools, respectively, on the cost of tools and materials. The article presents some experimental results concerning indicators of performance and quality of abrasive instruments with ceramic and organic bond by sharpening of circular saws with steel teeth and made appropriate recommendations for their use.